2D Ductile Transition Metal Chalcogenides (TMCs): Novel High‐Performance Ag2S Nanosheets for Ultrafast Photonics. Issue 6 (19th December 2019) - Feng, Jiangjiang; Li, Xiaohui; Shi, Zhaojiang; Zheng, Chuang; Li, Xuwei; Leng, Deying; Wang, Yamin; Liu, Jie; Zhu, Lujun
Abstract: As a member of the 2D transition metal chalcogenides (TMCs), 2D Ag2 S with large absorption coefficient, broadband optical response, extraordinary metal‐like ductility, high plastic deformation strain, unique layered structure, and very low solubility has offered a platform for achieving tremendous success in various fields. Great achievements have been made in exploring the linear optical, mechanical, and photoelectric properties of 2D Ag2 S nanosheets. However, the nonlinear optical properties of 2D Ag2 S nanosheets and their applications in ultrafast photonics have not been studied. The saturable absorption property of 2D Ag2 S nanosheets is experimentally illustrated at the telecommunication band with a large optical modulation depth of 15.5% and a low saturable intensity of 250.4 MW cm −2 . Moreover, the 229th harmonic soliton molecule with repetition rate of 1.1 GHz based on 2D Ag2 S saturable absorber is realized at the telecommunication band for the first time to the authors' knowledge. Thankfully, 2D Ag2 S nanosheets display excellent nonlinear optical properties suggesting that this may open a new door for advanced photonic devices based on 2D Ag2 S nanosheets. Abstract : As a member of the 2D transition metal chalcogenides (TMCs), 2D Ag2 S with large absorption coefficient, broadband optical response, and unique layered structure has offered a platform for achieving tremendous success in various fields. Herein, an Ag2 S saturable absorber (SA) is incorporated into an Er‐doped fiber laser to achieve a 229th harmonic soliton molecule, corresponding to a repetition frequency of 1.1 GHz for the first time.